2015
DOI: 10.1103/physrevlett.114.105303
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Quantum Glass of Bosons in a Random Potential in Two Dimensions

Abstract: We present a quantum Monte Carlo study of the "quantum glass" phase of the 2D Bose-Hubbard model with random potentials at filling ρ = 1. In the narrow region between the Mott and superfluid phases the compressibility has the form κ ∼ exp(−b/T α ) + c with α < 1 and c vanishing or very small. Thus, at T = 0 the system is either incompressible (a Mott glass) or nearly incompressible (a Mott-glass-like anomalous Bose glass). At stronger disorder, where a glass reappears from the superfluid, we find a conventiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Such phases have also been seen in other materials [26][27][28][29] and in quantum Monte Carlo simulations [30][31][32][33][34].…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Such phases have also been seen in other materials [26][27][28][29] and in quantum Monte Carlo simulations [30][31][32][33][34].…”
mentioning
confidence: 61%
“…Any such BoseHubbard-like model may be treated using the methods outlined here, with the microscopic differences appearing only in the UV-scale starting values of the flow parameters. This prediction lends weight to previous numerical quantum Monte-Carlo work [31,34]. It may also explain the controversy over the existence of a direct MI/SF transition at the tips of the Mott lobes in the disordered Bose-Hubbard model: previous works which used compressibility as the criterion for the onset of a glassy phase will necessarily have missed the transition between the Mott insulator and the Mott glass.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Numerically, q appears to be bounded from above by the value of the variance κ = ij [ n i n j − n i n j ]. Previous studies have shown that the variance is suppressed near the tip of the Mott lobes [38,39], with some suggesting that it vanishes entirely [66,67]. The suppression of κ results in the corresponding suppression of q in the vicinity of the tips of the Mott lobes, where we would in any case expect local mean-field theory to break down.…”
Section: Mean-field Phase Diagrammentioning
confidence: 81%
“…For the vertices defined by Eqs. (8) and (9) of the main text, we have to distinguish two cases: the directed loop either hits a unit operator, or any other operator. For the former case, the path goes straight through the subvertex with probability 1 and changes its vertex type.…”
Section: Solution Of the Directed-loop Equationsmentioning
confidence: 99%